1981
DOI: 10.1103/physrevc.24.1628
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear levels inLu176

Abstract: The nuclear structure of '"Lu has been studied with the (t,u) reaction on an isotopically enriched target of '"Hf using a 17 MeV triton beam and a quadrupole-triple-dipole-type spectrometer. These measurements were combined with published (n, P), (n,e ), and (d,p) data to construct a level scheme for ' Lu. The Nilsson model including Coriolis coupling c'lculations has been used to interpret the level structure. The previously known Nilsson configurations 7/2+ f404] + 7/2 [514], 7/2+[404] -7/2 f514], 7/2+[404] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The 1+ to 5+ members of Balodis et al [19] were confirmed via the transitions to the K =1+ band, but two suggested weak intraband transitions could not be detected. The 6+ level of Balodis et al [19] [19], and the Nilsson configuration was assigned by Dewberry et al [20]. The members from I =2 to 4 could be clearly confirmed [ Fig.…”
Section: Uncertainties Of the Level Energiesmentioning
confidence: 67%
See 3 more Smart Citations
“…The 1+ to 5+ members of Balodis et al [19] were confirmed via the transitions to the K =1+ band, but two suggested weak intraband transitions could not be detected. The 6+ level of Balodis et al [19] [19], and the Nilsson configuration was assigned by Dewberry et al [20]. The members from I =2 to 4 could be clearly confirmed [ Fig.…”
Section: Uncertainties Of the Level Energiesmentioning
confidence: 67%
“…In their work, the level energies are based on the reference energy of 126.5+4 keV for the isomeric state [17]. Additional levels were postulated based on a (t, a) measurement by Dewberry et al [20] including the assignment of gamma transitions measured by Balodis et al [19];furthermore, the excitation energy of the isomer could be determined to 123+2 keV. However, it was not yet possible to establish a level that could decay to both, the ground state an, d to the isomer.…”
Section: A Previous Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-resolution gamma-spectroscopic studies were performed using the 175 Lu(n,γ) 176 Lu reaction at the GAMS spectrometer at ILL, Grenoble [18,19,20], using HPGe detectors [19,21], and using the 176 Yb(p,n) 176 Lu reaction at the Berkeley cyclotron [22]. The 177 Hf(t,α) 176 Lu reaction was studied at Los Alamos using a Q3D magnetic spectrograph [23], and the 175 Lu(d,p) 176 Lu reaction was analyzed using the Q3D spectrograph at the Munich tandem accelerator [19]. Obviously, the s-process branching at A = 176 depends also on the neutron capture cross sections.…”
Section: Equilibriummentioning
confidence: 99%